2017
DOI: 10.1161/hypertensionaha.116.08839
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Ambient PM 2.5 on Hypertension and Blood Pressure and Attributable Risk Among Older Chinese Adults

Abstract: Long-term exposure to ambient fine particulate pollution (PM2.5) has been associated with cardiovascular diseases. Hypertension, a major risk factor for cardiovascular diseases, has also been hypothesized to be linked to PM2.5. However, epidemiological evidence has been mixed. We examined long-term association between ambient PM2.5 and hypertension and blood pressure. We interviewed 12,665 participants aged 50 years and older and measured their blood pressures. Annual average PM2.5 concentrations were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(98 citation statements)
references
References 47 publications
(64 reference statements)
8
79
2
3
Order By: Relevance
“…Dong et al (2013) found statistically significant associations with prevalent hypertension for three-year average PM 10 in a Chinese population (OR: 1.12, 95% CI: 1.08, 1.16 per 19 μg/m 3 ) [12]. More recently, Lin et al (2017) observed a 10 μg/m 3 increase in one-year average PM 2.5 associated with higher odds of hypertension (OR 1.14, 95% CI: 1.07, 1.22) and Liu et al (2017) found an IQR increase (41.7 μg/m 3 ) in 9-month average PM 2.5 to be associated with 1.11 (95% CI: 1.05, 1.17) times the odds of hypertension [46, 47]. …”
Section: Discussionmentioning
confidence: 99%
“…Dong et al (2013) found statistically significant associations with prevalent hypertension for three-year average PM 10 in a Chinese population (OR: 1.12, 95% CI: 1.08, 1.16 per 19 μg/m 3 ) [12]. More recently, Lin et al (2017) observed a 10 μg/m 3 increase in one-year average PM 2.5 associated with higher odds of hypertension (OR 1.14, 95% CI: 1.07, 1.22) and Liu et al (2017) found an IQR increase (41.7 μg/m 3 ) in 9-month average PM 2.5 to be associated with 1.11 (95% CI: 1.05, 1.17) times the odds of hypertension [46, 47]. …”
Section: Discussionmentioning
confidence: 99%
“…High blood pressure (BP) ranked the first leading risk factor for cardiovascular morbidity and mortality . In the past several years, a growing body of epidemiological studies has examined whether long‐term exposures to ambient fine particulate matter (with an aerodynamic diameter ≤2.5 μm; PM 2.5 ) pollution increase the risk of hypertension, but the findings are inconsistent . The inconsistent results may be attributable to the heterogeneity in particulate matter sizes or constituents between geographic regions.…”
Section: Introductionmentioning
confidence: 99%
“…In another study among older Chinese adults, it was found that long-term exposure to ambient fine particle pollution contributed significantly to hypertension in this population group (76). It was also observed that higher consumption of fruit might mitigate, whereas overweight and obesity could enhance this pollution-induced risk of hypertension (76).…”
Section: Clinical Evidence Of Nutritional Modulation Of Environmentalmentioning
confidence: 94%
“…In another study among older Chinese adults, it was found that long-term exposure to ambient fine particle pollution contributed significantly to hypertension in this population group (76). It was also observed that higher consumption of fruit might mitigate, whereas overweight and obesity could enhance this pollution-induced risk of hypertension (76). Most of all, interactions between nutrition and air pollution are particularly critical during developmental phases, and thus could possibly alter the odds of congenital heart defects in offspring (77).…”
Section: Clinical Evidence Of Nutritional Modulation Of Environmentalmentioning
confidence: 94%